2018
DOI: 10.1111/desc.12769
|View full text |Cite
|
Sign up to set email alerts
|

When causality shapes the experience of time: Evidence for temporal binding in young children

Abstract: It is well established that the temporal proximity of two events is a fundamental cue to causality. Recent research with adults has shown that this relation is bidirectional: events that are believed to be causally related are perceived as occurring closer together in time—the so‐called temporal binding effect. Here, we examined the developmental origins of temporal binding. Participants predicted when an event that was either caused by a button press, or preceded by a non‐causal signal, would occur. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…To conclude, the findings reported in the present study add to a small but growing body of evidence demonstrating an early-developing bidirectional relation between time and causality (Blakey et al, 2018;Lorimer et al, 2017). The current study extends this research by showing that children's causal impressions can qualitatively alter their temporal experience-through the reordering of events to match a causal interpretation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To conclude, the findings reported in the present study add to a small but growing body of evidence demonstrating an early-developing bidirectional relation between time and causality (Blakey et al, 2018;Lorimer et al, 2017). The current study extends this research by showing that children's causal impressions can qualitatively alter their temporal experience-through the reordering of events to match a causal interpretation.…”
Section: Discussionsupporting
confidence: 81%
“…Although Cavazzana et al concluded that this type of binding was a late-emerging phenomenon, their findings contrast with those of some recent studies using simplified child-friendly tasks. In these tasks, rather than retrospectively reporting the time at which an event occurred, participants either anticipated when they expected a target event (e.g., a rocket on a screen launching) to occur following an initial event (keypress or non-causal signal, Blakey et al, 2018), or gave a categorical estimation of the interval between the two events (Lorimer et al, under review). Children in both of these studies showed a binding effect-they were more likely to perceive the duration between two events to be shorter when there was a causal connection between them (i.e., when the rocket launch was caused by a keypress as opposed to preceded by an arbitrary signal).…”
Section: Causality Influences Children's and Adults' Experience Of Tementioning
confidence: 99%
“…As mentioned previously, it has been suggested that these instances of temporal binding occur as a result of a belief in causality having a top‐down influence on perception. Noting that temporal proximity can serve as a cue to causation, researchers have suggested that the psychological relation between time and causation is bidirectional (Blakey et al, 2019; Buehner, 2012; Vuorre, 2017): Not only does the timing of events influence causal beliefs, causal beliefs, in turn, have a top‐down influence on the perception of the timing of events, such that events believed to stand in a cause–effect relation to each other are perceived as occurring closer together in time. (See also Ma, Chen, Kording, & Wei, 2013, who draw on a similar idea to develop a Bayesian cue combination model of temporal binding.…”
Section: Temporal Binding and Causationmentioning
confidence: 99%
“…Both phenomena—temporal binding and causal reordering—have been connected with basic Humean assumptions known to inform causal learning: the assumption that causes are temporally contiguous with their effects and the assumption that causes precede their effects, respectively. More specifically, it has been suggested that temporal binding and causal reordering are brought about by processes that align the subjective timing of two causally related events with those basic Humean assumptions about causality—by making the events appear more contiguous with each other in the case of temporal binding, or by reordering so that the presumed cause is perceived as preceding the presumed effect (Bechlivanidis & Lagnado, 2016; Blakey et al, 2019; Buehner, 2012; Vuorre, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The varieties of temporal ability have also been explored in considerable detail (see e.g. from [19][20][21][22][23]), with some underlining the fundamental role of temporal contiguity in cuing causal inference (see e.g. [24]).…”
Section: Spatial and Spatial-temporal Cognitionmentioning
confidence: 99%